Corporate social responsibility in Islamic bank: review of one decade of research and future directions - Fauzan Fuadi; Selly Puspita Sari; Sunarmi Sunarmi; Andi Mulyono; Syriac Nellikunnel Devasia (Universitas Islam Negeri Walisongo Semarang, 2025)
Purpose - This study aims to systematically review the literature on corporate social responsibility in Islamic banks over the past decade, identifying key trends, determinants, impacts, and future research directions. Method - The systematic literature review methodology followed the PRISMA protocol to ensure a rigorous selection and evaluation process. The study analysed 25 papers from the Scopus database. Result - Findings suggest that CSR disclosure, governance structure, and regulatory support significantly influence the effectiveness of CSR in Islamic banks. While some studies show a positive relationship between CSR and financial performance, others show that the impact is context-dependent, varying across regulatory environments and socio-cultural dynamics. This study also highlights the methodological diversity in CSR research, with content analysis, regression analysis, and surveys being the most frequently used approaches. Implication - This study enhances academic and practical understanding of CSR in Islamic banking by analysing key internal and external determinants, synthesising CSR trends and challenges, and suggesting avenues for future research. Originality - This study integrates a holistic view of CSR trends and outlines a future research agenda. The findings provide valuable guidance for academics, practitioners, and policymakers on improving CSR implementation in Islamic banking.